Comorbidity as a predictor of racial and ethnic disparities in cancer in the United States population - Maxwell Akonde; Rajat Das Gupta; Ottovon Bismark Dakurah; Reston Hartsell (Elsevier, 2021)
Aims: This study aims to examine the racial and ethnic disparity in cancer prevalence and determine if comorbidities can explain this disparity. Study design: This was a cross-sectional study. Methods: The study examined cancer prevalence among adults who self-identified as White, Black, and Other races in the US population according to data from the 2017 National Health Interview Survey. Results: Cancer was 58.5% [OR = 0.415; 95% CI: 0.346-0.498] and 57.5% [OR = 0.425; 95%CI: 0.346-0.522] more likely to be found in the White compared to the Black adults and White compared to Other race adults, respectively. After adjusting for the comorbidities, the odds of cancer in White adults increased marginally compared to Black adults [OR = 0.407; 95%CI: 0.338-0.490] and decreased marginally compared to Other race adults [OR = 0.462; 95%CI: 0.374-0.569] even though the odds remained significant. Ever smoking, age of 50 years or more, Former and current alcohol consumption, overweight and obesity, being female and physical inactivity were found to be significantly associated with higher odds of cancer. Conclusions: This study did identify a racial and ethnic disparity in cancer prevalence between White and Black adults and White and Other adult races. However, this racial and ethnic disparity could not be explained by comorbidities.